Analysis of satisfiers and dissatisfiers in online hotel reviews on social media. Issue 9 (12th September 2016) - Kim, Bona; Kim, Seongseop; Heo, Cindy Y.
Abstract : Purpose: The purpose of this study is to analyze online hotel reviews produced by customers to identify and compare factors known as satisfiers and dissatisfiers based on Herzberg's two-factor theory. This approach was applied to compare full-service and limited-service hotels, which can show different levels of customer expectation. Design/methodology/approach: A content analysis of 919 satisfaction- and dissatisfaction-indicating reviews of 100 hotels in both full-service and limited-service hotel segments in New York City on Trip Advisor was conducted. Findings: Results show that satisfiers and dissatisfiers in full-service hotels were distinct, with the exception of two common service-related factors, namely, "staff and their attitude" and "service". On the other hand, "staff and their attitude" and four room facilities-related factors, "room cleanliness/dirtiness", "bed", "bathroom" and "room size", were revealed as common satisfiers and dissatisfiers in limited-service hotels. To fulfill customer satisfaction and resolve dissatisfaction in both full-service and limited-service hotels, satisfiers and dissatisfiers should be highlighted according to the hotel class; the most critical factor is "staff and their attitude". Practical implications: Analysis of online hotel reviews provides understanding of customers' satisfiers and dissatisfiers, and the results are very useful to hotel management. Therefore, hotel operators should monitor electronic word-of-mouth, recognizing and acting upon previous and current customers' satisfactory and unsatisfactory reactions. Originality/value: As technologies such as social media develop, customers are increasingly sharing their satisfactory and unsatisfactory experiences on consumer-generated online review sites. These have become a major source of information not only for customers deciding on a hotel stay but also for hotel managers trying to understand their customers and competitors.